Quality assessment of local and franchise beef and chicken burgers - Babji, Abdul Salam; M. N., Nuri; Jaksa, Suherman; Mohd Yusof, Seri Chempaka (Universiti Putra Malaysia Press, 2000)
Six brands of local beef and chicken burgers, three brands of franchise beef and two brands of franchise chicken burgers were evaluated for proximate composition, myoglobin and meat content, colour (L, a, b values) and microbiology composition i.e. Total Plate Count (CFU/gm), Coliform and Escherichia coli Counts (MPN/gm), Staphylococus aureus Count (CFU/gm) and presence of Salmonella sp. All franchise beef burgers had higher protein and moisture contents (except burger C) and lower carbohydrate content than the local brands. No significant differences (p > 0.05) in fat, ash and crude fibre contents were observed between local brands and franchise beef burgers. Most local brands of chicken burgers had lower levels of protein and moisture and higher levels of fat, fibre and carbohydrate than the franchises. No significant differences (p > 0.05) in ash content was observed between the local brands and franchise chicken burgers. All beef burgers had low myoglobin and meat contents «65%) with the exception of AI, FI and GI burgers. Chicken burgers, EI, FI and franchise burger B had higher meat content (>65%) than the others. All beef and chicken burgers had higher 'L' values which ranged between 45.13 % to 53.68% and 62.75 % to 72.48% respectively except FI which was darker. Local brands of beef burgers had a higher 'a' value compared to the franchises and all chicken burgers had a low 'a" value except FI which was redder. Low Total Plate Count, Coliform and E. coli counts were detected in all burger samples. S. aureus counts in most local brands of beefand chicken burger samples were higher than the franchises which ranged from 2 to 11 CFU/gm sample and 6 to 22 CFU/gm sample respectively. Salmonella sp was not present in all burger samples.